MO1057: Cost-Analysis of a Clinical Workflow for Diagnosis of Inherited Kidney Diseases. (3rd May 2022) - Cirillo, Luigi; Becherucci, Francesca; Bellelli, Stefania; Mazzinghi, Benedetta; Raglianti, Valentina; Lugli, Gianmarco; Landini, Samuela; Palazzo, Viviana; Tiberi, Lucia; Vaglio, Augusto; Anders, Hans-Joachim; Romagnani, Paola
Abstract: BACKGROUND AND AIMS: In the last decade, the use of whole-exome sequencing techniques (WES) has provided many insights into inherited kidney diseases that are thought to represent at least 10%–15% of cases of end-stage CKD [1 ]. However, among others, cost concerns limit the widespread of genomics use in daily practice [1, 2 ]. Publicly funded genomic testing is restricted in most health care systems [2 ]. Consequently, the evaluation of cost-effectiveness is urgently required in order to establish genomic sequencing as a standard diagnostic test for nephropathic patients. The aim of this study was to perform a cost-analysis of genetic testing use in a diagnostic workflow. METHOD: We recently set up a diagnostic workflow for the selection of patients that should undergo genetic testing in the suspicion of a genetic disease. This algorithm is applied by a network of nephrology centres on the regional territory. Selected patients are referred to a tertiary centre, Meyer University Hospital of Florence (Italy), for genetic diagnosis by WES. We enrolled paediatric and adult patients referred to the outpatient service based on the pre-specified clinical criteria. All the patients underwent genetic testing from 2018 to June 2021. We conducted a cost-analysis in two parts: (1) assessment of the cost-effectiveness cut-off; and (2) exploratory modeled cost-analysis using WES in different phases of the diagnostic trajectory. As a surrogate of the cost-effectiveness analysis, we calculated the cost-effectiveness cut-off, indicating the amount of expenses for diagnostic examinations at which WES sequencing would be cost-effective. For the exploratory cost-analysis, we defined two diagnostic trajectories: Model I, considering an ideal complete diagnostic pathway and late use of WES; and Model II, considering an early use of WES allowing to save a certain number of examinations. Genomic and non-genomic investigations were obtained from local practice, available clinical evidence and guidelines. We then calculated the cost per diagnosis according to each Model for different clinical categories and for the whole study population using the diagnostic rates of this study. We considered only direct medical costs, based on the regional health reimbursement system, which is comprehensive of materials and human resources. The prices are expressed in euros. The analysis was conducted from a regional healthcare system perspective. RESULTS: The analysis included 402 patients. WES performed after the standard non-conclusive diagnostic work-up (at a mean cost of €2992/patient) resulted in cost-effectiveness at a cost of <€2004/patient in the study population. Looking at different clinical categories, WES was cost-effective at a cost ranging from €3336 to €770. Overall, the exploratory cost-analysis showed Model II as cost reducing in comparison to Model I. The mean cost per diagnosis in Model I with late use of WES was estimated at €7700. Early use of WES in Model II had an estimated cost per diagnosis of €6340, leading to a cost saving of €1360/patient tested. Regarding the single clinical categories, the highest cost saving per diagnosis was obtained in podocytopathies (Model I: €13.010 versus Model II: €7261). The early use of WES produced a slight increase in estimated costs per diagnosis for tubulopathies, as well as for ciliopathies, while for syndromic CKD and metabolic kidney disorders, the costs per diagnosis did not result in major changes. CONCLUSION: Early use of WES in the diagnostic pathway of inherited diseases, guided by a framework of specific criteria, is feasible and has the potential to produce substantial cost savings in healthcare.